High resolution magnetic resonance imaging in adults with partial or secondary generalised epilepsy attending a tertiary referral unit. Issue 4 (October 1995) - Li, L M; Fish, D R; Sisodiya, S M; Shorvon, S D; Alsanjari, N; Stevens, J M
Abstract : In the past the underlying structural abnormalities leading to the development of chronic seizure disorders have usually only been disclosed by histological examination of surgical or postmortem material, due to their often subtle nature that was beyond the resolution of CT or early MRI. The MRI findings in 341 patients with chronic, refractory epilepsy attending The National Hospital for Neurology and Neurosurgery and Chalfont Centre for Epilepsy are reported. Studies were performed on a 1.5 Tesla scanner with a specific volumetric protocol, allowing the reconstruction of 1.5 mm contiguous slices throughout the whole brain. Direct visual inspection of the two dimensional images without the use of additional quantitative measures showed that 254/341 (74%) were abnormal. Twenty four (7%) patients had more than one lesion. The principal MRI diagnoses were hippocampal asymmetry (32%), cortical dysgenesis (12%), tumour (12%), and vascular malformation (8%). Pathological confirmation was available from surgical specimens in 70 patients and showed a very high degree of sensitivity and specificity for the different entities. The advent of more widely available high resolution MRI should make it possible to identify the underlying pathological substrate in most patients with chronic partial epilepsy. This will allow a fundamental reclassification of the epilepsies for both medical and surgical management, with increasing precision as new methods (both of acquisition and postprocessing) are added to the neuroimaging battery used in clinical practice.